Biologic exposure of short duration results in a marked reduction in cumulative surgical rates in Malaysian patients with inflammatory bowel disease - Nik Muhamad Affendi, Nik Arsyad; Xin Hui, Khoo; Chuah, Kee Huat; Hilmi, ida normiha (2022)
INTRODUCTION: Crohn disease (CD) is a chronic progressive disease that is associated with high surgical rates. In view of our recent practice is starting biologic therapy early, we sought to determine whether there were differences in surgical rates between patients who were exposed or not exposed to biologic therapy. METHODOLOGY: This was a retrospective, single-centre study conducted in a tertiary centre in Malaysia. The biologic- exposed group was defined as any patient with exposure for at least 6-8 weeks. Demographics, clinical characteristics and time to significant surgical intervention (ie bowel resection) were recorded and cumulative surgical rates were calculated. RESULT: A total of 158 patients were recruited: 85 from the biologic-exposed cohort and 73 from the non-biologic cohort. Baseline demography was as follows: Male 56.3% Female 43.7%; Malays 21.5% Chinese 33.5% Indians 43.0%. Median duration of disease was 11.9 years (1.4, 30.4). Differences seen in terms demographics, disease location and behavior at diagnosis between the two cohorts were not significant. For the biologic group, median time to commencing therapy was 26.4 months (0.0, 165.6) and median duration of therapy was 13 months (IQR 1.5,130.0). The biologic-exposed group had significantly lower cumulative surgical rates compared to the non-biologic group; 2.3% versus 21.9% at 1 year; 7.3% versus 31.5% at 5 years and 15.6% versus 39.7% at ten years. CONCLUSION: Surgical rates were significantly lower in CD patients who are biologic-exposed even for a short duration. This confirms that the role of biologic therapy in altering the disease progression of CD, even in a limited resource setting.